Sequência didática: uso de mapas mentais e mapas conceituais no auxílio à aprendizagem significativa do conceito de velocidade média, com foco na alfabetização científica - Santana, Alexandre Baratta (2019)
The teaching of traditional physics, in which the teacher is the protagonist of the teaching-learning process, and the students are passive beings and mere recipients of information is already dated and notoriously inefficient. In this context, this work was designed to contribute to the discussion of what we can do to motivate our students to take part in the teaching-learning process, aiming at its protagonism. This work was inspired by David Ausubel's Meaningful Learning, uses as teaching tools the Mind Mapping and Concept Maps, and seeks to contribute to a discussion about Scientific Literacy in the classroom. For this, we work in the classroom ways to make the studied subjects meaningful to the students, taking into consideration their experiences, their particular way of explaining the phenomena they observe, their way of perceiving and interacting with the world, which are strongly influenced by common sense. During the elaboration of this work, the subjects of physics, especially Average Speed, were approached in the classroom in order to raise reflections about the use of technological advances in our daily lives, fostering discussions about how the development of science influences our lives. We seek to make it clear to students that what they have to learn in physics classes has a direct connection to their daily life. We seek to provoke the perception that students already know physics, but in their own way. Classes have become an environment in which everyday life and formal science, with their method and language, can meet in a way that makes learning enjoyable, allowing for a world of discovery. We sought to spark interest in science learning by working in the classroom at different times when we discussed the benefits and risks brought by scientific development to our lives, and that the technologies that make our lives comfortable are the result of a long and long process. hard development. We realized that exploring what students already know about a particular theme contributes strongly to deepen their knowledge.